2021
DOI: 10.4103/jfmpc.jfmpc_2493_20
|View full text |Cite
|
Sign up to set email alerts
|

Cataract and Associated Factors Among OPD Attendees in a Teaching Institute of North East India

Abstract: Background: In India 66% of blindness among individuals aged 50 yrs and above is attributable to cataract. Cataract has multiple etiologies and many of them are modifiable. But data regarding burden and correlates of cataract among OPD attendees in Northeast India are insufficient. Objectives: To estimate the proportion of cataract among the attendees of ophthalmology OPD of a teaching hospital of Northeast India and to study the factors associated with it. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In our study, we found that the most of the study cataract patients were from urban areas (56.5%). Das et al [18] reported that proportion of cataract among participants from urban and rural areas were 38% and 35.4% respectively, which was not significant (P > 0.05).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In our study, we found that the most of the study cataract patients were from urban areas (56.5%). Das et al [18] reported that proportion of cataract among participants from urban and rural areas were 38% and 35.4% respectively, which was not significant (P > 0.05).…”
Section: Discussionmentioning
confidence: 93%
“…Das et al [18] reported in their study that among the cataract study patients, (55.5%) were females, while males were 44.5% (ratio female to male 1.3:1).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, socio-cultural factors of patients, their health systems, and awareness play an important role in this uptake, which needs to be explored further. Moreover, a probable reason for the central and north-eastern zones to have fewer cataract surgeries may be due to disparities in health infrastructure, geographic remoteness, and differences among the participants studied, which can also impede access challenges ( 31 , 32 ). Moreover, health-seeking behaviour also varies between the regions, which could also be a probable reason for this difference ( 33 ).…”
Section: Discussionmentioning
confidence: 99%